Functional Role of Resveratrol in Inducing Apoptosis in Breast Cancer Subtypes via Inhibition of Intracellular Fatty Acid Synthase - Ping Li; Yan Liang; Xiaofeng Ma (Molecules)
Fatty acid synthase (FASN) is frequently overexpressed in human breast cancer and has emerged as a potential therapeutic target. Resveratrol has been shown to inhibit FASN activity in vitro through both fast-reversible and slow-irreversible mechanisms. In this study, resveratrol reduced intracellular fatty acid levels by inhibiting FASN activity and downregulating its expression across various breast cancer subtypes, including SK-BR-3, MCF-7, and MDA-MB-231 cells. Knockdown of FASN via small interfering RNA (siRNA) further enhanced resveratrol-induced cytotoxicity. Resveratrol significantly suppressed cell viability and triggered apoptosis, as evidenced by increased cleavage of poly(ADP-ribose) polymerase (PARP) and disruption of Bcl-2 family protein balance. Furthermore, resveratrol inhibited key signaling pathways involved in cell proliferation and survival, notably FAK, AKT, and ERK1/2. FASN silencing by siRNA also modulated the activation states of these signaling proteins. Collectively, these findings support resveratrol as a promising anti-cancer candidate that induces apoptosis in diverse breast cancer subtypes via FASN inhibition.